ANALISIS KEPUASAN DAN LOYALITAS PELANGGAN TERHADAP PENINGKATAN PENERIMAAN NEGARA BUKAN PAJAK DI RUMAH SAKIT MARINIR CILANDAK DENGAN METODE SEM PLS - Radyawanto , Aris Setyo; Suhardi, Suhardi; Hartanto, Adie; Guyana, Daniel; Kiswara, Geger Jaka (Journal of Industrial Engineering & Management Research, 2022)
Customer satisfaction is one of the factors that affect customer loyalty. A good experience will always be remembered by customers and will certainly recommend the experience to others, and will also make these customers will visit again in the future. If this is achieved, it will affect the income of a business entity, both private and government. Various ways are carried out by business entities to increase their income, one of which is by evaluating the performance of management and employees who work in providing good service to customers. The performance evaluation does not only come from the head of the business entity, but can also come from customer responses. It is through the responses of these customers that it is considered the most objective in assessing all instruments related to the business system of the business entity.The purpose of this study is to find a correlational relationship between several variables that affect the increase in Non-Tax State Revenue (PNBP), namely customer satisfaction and customer loyalty. Primary data was obtained from questionnaires to 100 customers of the Cilandak Marine Hospital and secondary data was obtained from annual performance reports. The data obtained were processed using the PLS SEM method. Evaluation is done for the outer model (measurement model) and then the Inner model. The results of testing the relationship between variables indicate that customer satisfaction does not have a direct and significant effect on increasing PNBP and customer loyalty has a direct and significant effect on increasing PNBP. With the results above, it can be used as a basis by management to make strategies to improve the performance of the staff.